The efficacy and safety of asleep and awake subthalamic deep brain stimulation for Parkinson’s disease patients: A 1-year follow-up - Chen, Wanru; Zhang, Changming; Jiang, Nan; Jiang, Lulu; Guo, Qiyu; Gu, Jing; Xian, Wenbiao; Ling, Yuting; Liu, Yanmei; Zheng, Yifan; Wu, Lei; Yang, Chao; et al. (Frontiers in Aging Neuroscience, 2023)
Introduction: Traditional DBS is usually conducted under local anesthesia (LA) which is intolerable to some patients, DBS under general anesthesia (GA) was opted to extended surgical indication. This study aimed to compare the efficacy and safety of bilateral subthalamic deep brain stimulation (STN-DBS) for Parkinson’s disease (PD) under asleep and awake anesthesia state in 1-year postoperative follow-up. Methods: Twenty-one PD patients were assigned to asleep group and 25 patients to awake group. Patients received bilateral STN-DBS under different anesthesia state. The PD participants were interviewed and assessed preoperatively and at 1-year postoperative follow-up. Results: At 1-year follow-up, compared surgical coordinate in two groups, the left-side Y of asleep group showed more posterior than awake group (Y was -2.39±0.23 in asleep group, -1.46±0.22 in awake group, p=0.007). Compared with preoperative OFF MED state, MDS-UPDRS III scores in OFF MED/OFF STIM state remained unchanged, while in OFF MED/ON STIM state were significantly improved in awake and asleep groups, yet without significant difference. Compared with preoperative ON MED state, MDS-UPDRS III scores in ON MED/OFF STIM, and ON MED/ON STIM state remained unchanged in both groups. In non-motor outcomes, PSQI, HAMD, and HAMA score significantly improved in asleep group compared to awake group at 1-year follow-up (PSQI, HAMD, and HAMA score in 1-year follow-up were 9.81±4.43; 10.00±5.80; 5.71±4.75 in awake group, 6.64±4.14; 5.32±3.78; 3.76±3.87 in asleep group, p=0.009; 0.008; 0.015, respectively), while there was no significant difference in PDQ-39, NMSS, ESS, PDSS score, and cognitive function. Anesthesia methods was significantly associated with improvement of HAMA and HAMD score (p=0.029; 0.002, respectively). No difference in LEDD, stimulation parameters and adverse events was observed between the two groups. Discussion: Asleep STN-DBS may be considered a good alternative method for PD patients. It is largely consistent with awake STN-DBS in motor symptoms and safety. Yet, it showed higher improvement in terms of mood and sleep compared to awake group at 1-year follow-up.